تحليل الطريقة المستعملة في تعليم علم النحو في المدرسة المتوسطة الإسلامية بمعهد دار الإخلاص مندايلينج ناتل - Sapril Efendi; Zulpina; Isra Hayati Darman (PT. Willy Print Art, 2025)
The background of this study is to determine the method of learning nahwu science because nahwu science is a very important science for understanding Arabic, the Qur'an, the Hadith of the Prophet SAW and classical books written by previous scholars, and the reason the researcher chose the Daar Al-Ikhlash Islamic boarding school as a place of research because its students have achievements in the field of qiroat al-kutub. This study aims to analyze the methods used in learning nahwu science, implementation, supporting and inhibiting factors in the process of learning nahwu science at MTs Daar Al-Ikhlash Mandailing Natal. And the type of this research is qualitative descriptive research. And the method of data collection in this study through observation, interviews, and documentation of teachers and students. The results of the research conducted by the researcher: 1) the methods used by teachers in learning nahwu science are various methods, namely: qiyasiyah method, memorization method, muzakarah method, istiqroiyah method, and tathbiqi method. 2) the implementation of the nahwu science learning process at MTs Daar Al-Ikhlash Mandailing Natal through three steps, namely: preliminary activities, core activities, and closing activities. 3) supporting factors in the nahwu science learning process at this school are: additional study time, competitions at the end of the semester, tabliq activities, professional teachers, and the environment. While the inhibiting factors are: the students' previous educational background, and students' interest in learning. And the efforts made by teachers to overcome obstacles in the learning process and the application of nahwu science learning methods at MTs Daar Al-Ikhlash Mandailing Natal are: providing motivation to students, and emphasizing discipline.